Combustion instability analysis on a partially premixed swirl combustor by thermoacoustic experiments and modeling. (15th November 2020) - Zhu, Rongjun; Pan, Deng; Ji, Chenzhen; Zhu, Tong; Lu, Pengpeng; Gao, Han
Abstract: The combustion instability of a partially premixed swirl burner is investigated by experimental tests and numerical modeling. The experimental results show that the combustion dynamics of the partially premixed swirl combustor under different thermal power rates and equivalence ratios can be classified into three regimes: combustion noise, intermittent oscillation and limit cycle oscillation. The characteristics of each combustion regime are clarified: combustion noises occur with small pressure oscillation amplitudes and unapparent frequencies when the equivalence ratio approaches 1; the limit cycle oscillations present in strong single frequencies within the relative lower (6223–8563) and higher (10, 796–13536) ranges of Re number; the intermittent oscillations observed within a middle range (8634–10796) show multiple peaks in their spectrums. To obtain the relationship between flame transfer function and thermoacoustic modes of the combustor, the CFD/system identification and low order thermoacoustic network model are developed. The thermoacoustic modes are found to be influenced by the interactions between natural acoustic mode and flame response factors. The modeling results reveal that the intermittent oscillations show two modes with positive growth rates, while the limit cycle oscillations are dominated by one mode. Moreover, the combustion instability is found more sensitive to FTF but not acoustic boundary in the modeling. Highlights: Thermoacoustic modes of a partially premixed swirl combustor under different thermal power and equivalence ratio are studied. Experimental results show three combustion regimes: combustion noise, intermittent oscillation and limit cycle oscillation. The different combustion regimes originate from different thermoacoustic modes, i.e. the acoustic mode, the thermoacoustic mode and their coupling.